Balancing Competition and Collaboration in Early Childhood Through the Values of Fastabiqul Khairat and Ta’awun - Utsman, Ahmad Farid; Mu’awanah, Elfi; Kojin, Kojin; Puspitasari, Endang (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study examines the imbalance between competitive and collaborative practices in early childhood education, which may foster individualistic attitudes among children. While competition is commonly used to enhance learning motivation, previous studies have largely examined competition and collaboration separately, with limited attention to their integration within a coherent value-based pedagogical framework. Therefore, this study aims to analyze the integration of the values of fastabiqul khairat (striving to do good deeds) and ta'awun (mutual assistance) as a pedagogical approach to balancing competition and collaboration in early childhood learning. This research employed a qualitative descriptive design conducted at an Islamic-based early childhood education institution in Bojonegoro, Indonesia. The participants consisted of 3 teachers and 20 children selected through purposive sampling, and data were collected over a period of two months. Data were gathered through classroom observations, in-depth interviews, and documentation, and analyzed using thematic analysis with triangulation to ensure data validity. The findings reveal that implementing fastabiqul khairat promotes positive, prosocial competition, while ta'awun strengthens cooperation, empathy, and social awareness among children. This result indicates that value-based integration reshapes the competitive landscape. Transition from individual achievement to prosocial development. Furthermore, the study demonstrates that competition and collaboration can be complementary rather than opposing approaches in early childhood education. This study contributes to the development of Islamic early childhood education by proposing a novel value-based pedagogical framework that integrates Islamic principles into learning practices, particularly in the design of structured learning activities that combine prosocial competition and collaborative engagement